Ecological dichotomies of solar energy expansion: resilience in arid regions versus fragility in humid ecosystems - Jianhua Xiao; Panxing He; Yong Li; Mingjie Shi; Yang Li; Jun Ma (Frontiers in Plant Science)
The deployment of Utility-Scale Solar Energy (USSE) systems is increasingly recognized as a cornerstone strategy in mitigating climate change. However, the environmental ramifications of such extensive developments remain the subject of considerable debate, with marked regional variability in their ecological effects, particularly across different biomes. As such, there is a pressing need for comprehensive, systems-level investigations to evaluate the multifaceted environmental impacts of USSE in both arid and humid ecosystems. Here, we undertake an exhaustive assessment utilizing a high-resolution (10 m) dataset of photovoltaic (PV) station distributions across China, complemented by Landsat-derived NDVI remote sensing data from 2019 to 2023. This approach facilitates the quantification of the dynamic effects of PV infrastructure development on vegetation greenness (NDVImean and NDVImax), and allows for the assessment of scale-dependent ecological responses across two contrasting regions: the arid zone of Ningxia and the humid zone of Anhui. Our results indicate that in the arid region, the construction of PV facilities has a negligible effect on vegetation greenness, with inter-annual variations in NDVImean remaining consistently below 0.05, and no discernible change in NDVImax. In contrast, PV development in the humid region led to a dramatic deterioration in vegetation greenness, with NDVImean declining sharply from 0.42 to below 0.20—representing a reduction of over 50%, particularly during the growing season (April to October). Furthermore, the relationship between the scale of PV installations and their ecological impact in the humid region was characterized by a pronounced non-linearity, with large-scale PV plants (spanning >10,000 pixels) causing near-total vegetation collapse, driving NDVI toward near-zero. Collectively, these findings suggest that the sparse vegetation and enhanced microclimatic regulation characteristic of arid ecosystems provide greater resilience to external disturbances, whereas the high-biomass vegetation typical of humid regions is significantly more vulnerable to perturbations. Based on these insights, we advocate for the strategic prioritization of arid regions with greater ecological adaptability for future USSE development, alongside the incorporation of ecological restoration measures and the optimization of facility scale to mitigate potential environmental disturbances. Our study emphasizes the need for a synergistic approach to optimize both energy transition and ecological conservation in the context of regional variability, offering a solid scientific basis for the national-scale planning and site selection of photovoltaic energy projects.